2021
DOI: 10.3390/agronomy11061164
|View full text |Cite
|
Sign up to set email alerts
|

Strip Tillage and Crop Residue Retention Decrease the Size but Increase the Diversity of the Weed Seed Bank under Intensive Rice-Based Crop Rotations in Bangladesh

Abstract: Cropping under conservation agriculture (CA) has become increasingly attractive among farmers in recent years. However, weed control may be more difficult during the transition to CA from conventional establishment methods due to the reduction in tillage intensity. Conversely, CA changes to weed dynamics can alter the weed seed bank in the longer run. In Bangladesh’s intensively cropped rice-based rotations, the nature of weed seed bank shifts over time after adopting CA are poorly known. Two 2-year studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…Hence, the present study may have overestimated the likely abundance of germinable weed seeds, by creating suitable germination conditions for seed that are normally buried too deep in CT, and especially in SP, to germinate and/or emerge. However, in another study, we found a lower weed density and biomass, and fewer weed species in the weed seedbank in soils sampled to only 0-5 cm under the SP + 50% residue retention, compared to CT after only 2 years [16]. Dormant seeds in CT become viable to germinate by scarification, ambient CO 2 concentrations, and higher nitrate concentrations, which may lead to the production of a higher weed emergence of new weed species in plowed soils [17].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Hence, the present study may have overestimated the likely abundance of germinable weed seeds, by creating suitable germination conditions for seed that are normally buried too deep in CT, and especially in SP, to germinate and/or emerge. However, in another study, we found a lower weed density and biomass, and fewer weed species in the weed seedbank in soils sampled to only 0-5 cm under the SP + 50% residue retention, compared to CT after only 2 years [16]. Dormant seeds in CT become viable to germinate by scarification, ambient CO 2 concentrations, and higher nitrate concentrations, which may lead to the production of a higher weed emergence of new weed species in plowed soils [17].…”
Section: Discussionmentioning
confidence: 52%
“…The seedbank of the CT + 20% residue was more diversified (values 3.09 and 0.41, respectively) than the SP + 50% residue. In a similar study, which lasted only 2 years, Hossain et al [16] reported a more diversified seedbank of CT without residue (with diversity and dominance indices of 2.93 and 0.54, respectively), relative to the SP + 50% residue (indices of 2.44 and 0.90, respectively), even though that study sampled soils to 5 cm depth rather than 15 cm. In another study, Cardina et al [37] found a decrease in species diversity with the increasing number of tillage operations; their diversity indices were 0.6, 0.5, and 0.2 in NT, RT, and CT, respectively).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Many studies observed that reduced or zero tillage increased weed density and weed aboveground biomass [24,45]. In addition, strip-tillage with crop mulch could decrease the size, but increase the diversity of the soil seed bank when comparing with conventional tillage with no crop mulching [46]. Therefore, further studies with long term observation are needed in the future to determine the mechanisms of integrated weed management related to the soil physicochemical properties, nutrient uptake mechanisms of both crops and weeds, soil microbial community, and soil enzyme activities on the weed community composition and structure.…”
Section: Effects Of Weeds On Maize Growth and Yieldmentioning
confidence: 99%